Early endoscopic ultrasonography in acute biliary pancreatitis: A prospective pilot study - Anderloni, Andrea (World J Gastroenterol, 2015)
AIM: To investigate the clinical usefulness of early endoscopic ultrasonography (EUS) in the management of acute biliary pancreatitis (ABP). METHODS: All consecutive patients entering the emergency department between January 2010 and December 2012 due to acute abdominal pain and showing biochemical and/or radiological findings consistent with possible ABP were prospectively enrolled. Patients were classiﬁed as having a low, moderate, or high probability of common bile duct (CBD) stones, according to the established risk stratiﬁcation. Exclusion criteria were: gastrectomy or patient in whom the cause of biliary obstruction was already identified by ultrasonography. All enrolled patients underwent EUS within 48 h of their admission. Endoscopic retrograde cholangiopancreatography was performed immediately after EUS only in those cases with proven CBD stones or sludge. The following parameters were investigated: (1) clinical: age, sex, fever; (2) radiological: dilated CBD; and (3) biochemical: bilirubin, AST, ALT, gGT, ALP, amylase, lipasis, PCR. Association between presence of CBD stone at EUS and the individual predictors were assessed by univariate logistic regression. Predictors significantly associated with CBD stones (P < 0.05) were entered in a multivariate logistic regression model. RESULTS: A total of 181 patients with pancreatitis were admitted to the emergency department between January 2010 and December 2012. After exclusion criteria a total of 71 patients (38 females, 53.5%, mean age 58 ± 20.12 years, range 27-89 years; 33 males, 46.5%, mean age 65 ± 11.86 years, range 41-91 years) were included in the present study. The probability of CBD stones was considered low in 21 cases (29%), moderate in 26 (37%), and high in the remaining 24 (34%). The 71 patients included in the study underwent EUS, which allowed for a complete evaluation of the target sites in all the cases. The procedure was completed in a mean time of 14.7 min (range 9-34 min), without any notable complications.The overall CBD stone frequency was 44% (31 of 71), with a significant increase from the group at low pretest probability to that at moderate (OR = 5.79, P = 0.01) and high (OR = 4.25, P = 0.03) pretest probability. CONCLUSION: Early EUS in ABP allows, if appropriate, immediate endoscopic treatment and significant spare of unnecessary operative procedures thus reducing possible related complications.